Локализация функциональных структур в коленном суставе - Щегольков, А.Н. (Вестник зоологии, 1972)
Synovial processes of joints -- villi and foids are reaclive structures. They re formed in those sections of the joint where synovial liquid accumulates. Their localization in different animals depends on the joint biomechanics.